Anisotropies in structure and properties of hot-press sintered h-BN-MAS composite ceramics: Effects of raw h-BN particle size. Issue 2 (February 2019) - Niu, Bo; Cai, Delong; Yang, Zhihua; Duan, Xiaoming; Sun, Yangshan; Li, Hailiang; Duan, Wenjiu; Jia, Dechang; Zhou, Yu
Abstract: Effects of raw h -BN particle size from 0.5 μm to 11 μm on the phase compositions, texture degree, bending strength, fracture toughness and thermal conductivity of hot-press sintered h -BN-MAS composite ceramics were investigated. Larger h -BN grain can facilitate the nanocrystallization of MAS phase due to the inhibiting crystallization effect of h -BN on α-cordierite. Texture degree of h -BN-MAS composite ceramics increased significantly with increasing raw h -BN particle size, and the 11.0μmBN-MAS composite ceramic shows typical textured structure. The h -BN-MAS composite ceramics show anisotropy in mechanical properties and thermal conductivity, and the anisotropy increased significantly with increasing raw h -BN particle size. The 0.5μmBN-MAS sample shows excellent mechanical properties, and the 10μmBN-MAS sample shows strong anisotropy in thermal conductivity.